Los juegos de construcción y la motricidad fina en los niños del nivel inicial II de la Unidad Educativa Lauro Damerval Ayora de la ciudad de Loja, en el período 2021 – 2022 - Manchay Castillo, Kerly Leccy (2022)
Fine motor skills cover the development of early childhood and therefore the great value and importance of use with various creations that children can make and the challenges caused by their manipulation, seeking improvement, accuracy and coordination of arms and hands in order to strengthen their skills. In the present study, the objective was to determine how construction games help strengthen fine motor skills in children of the initial level II of the Lauro Damerval Ayora Educational Unit in the city of Loja in the period 2021 – 2022. The research was framed in a mixed approach because it was a process that allowed to investigate, collect, analyze and link quantitative and qualitative data, in the research; the scope was descriptive, where the characteristics and profiles of the children were detailed and described; The analytical-synthetic methods were used, which served to collect information and carry out the analysis of the variables investigated, and the inductive-deductive method, which helped to formulate the proposed objectives and establish the conclusions and recommendations. The technique used was a structured interview addressed to the teacher, and as an instrument an assessment scale adapted from the initial education curriculum, applied to 16 children aged from 4 to 5 years. The initial results showed that 81% of children were in the initiation and process parameter since they had not acquired fine motor skills, for which a guide based on construction games was designed and applied, verifying that 100% improved their fine motor skills in the classroom. Concluding that construction games are an effective strategy to improve fine motor skills, which provide fun learning, allowing children to acquire excellent writing skills and autonomy in daily life. Keywords: Fine motor, muscle tone, motor skills and construction games.